Boron nitride nanosheets as barrier enhancing fillers in melt processed composites1. Issue 10 (14th March 2015) - Xie, Shaobo; Istrate, Oana M.; May, Peter; Barwich, Sebastian; Bell, Alan P.; Khan, Umar; Coleman, Jonathan N.
<x xml:space="preserve">Abstract</x> In this work we have used melt-processing to mix liquid-exfoliated boron–nitride nanosheets with PET to produce composites for gas barrier applications.